Sepron, the sea serpent - Blade, Adam; Tucker, Ezra N. (Scholastic New York, 2007)
"Floods. Starvation. Fear. This is what awaits the people of Avantia's coast if Tom and Elenna cannot stop Sepron the Sea Serpent. The huge and terrifying beast lurks in eerie waters. All the fish have fled and no boats dare to pass. Tom and Elenna head to the coast, where things are worse than they even imagined. As they set off in a rickety rowboat, Tom can't help but wonder if they'll succeed so easily this time"--Page 4 of cover